The Role of Structural Maintenance of Chromosomes Complexes in Meiosis and Genome Maintenance: Translating Biomedical and Model Plant Research Into Crop Breeding Opportunities - Bolaños-Villegas, Pablo (Frontiers in Plant Science, 2021)
Cohesin is a multiunit protein complex from the structural maintenance of chromosomes (SMC) family, required for holding sister chromatids together during mitosis and meiosis. In yeast, the cohesin complex entraps sister DNAs within tripartite rings created by pairwise interactions between central ring units Smc1 and Smc3 and subunits such as the α-kleisin Scc1 (Rec8 in meiosis). The complex is an indispensable regulator of meiotic recombination in eukaryotes. In Arabidopsis and maize, the SMC1/SMC3 heterodimer is a key determinant of meiosis. In Arabidopsis, several kleisin proteins are also essential: SYN1/REC8 is meiosis-specific and is essential for double-strand break repair, whereas subunit AtSCC2 is important for synapsis and segregation. Other important meiotic subunits are the cohesin EXTRA SPINDLE POLES (AESP1) separase, the acetylase ESTABLISHMENT OF COHESION 1/CHROMOSOME TRANSMISSION FIDELITY 7 (ECO1/CTF7), the cohesion release factor WINGS APART-LIKE PROTEIN 1 (WAPL) in Arabidopsis (AtWAPL1/AtWAPL2), and the WAPL antagonist AtSWITCH1/DYAD (AtSWI1). Meiotic recombination is key to enriching desirable traits in commercial plant breeding. In this review, we highlight critical advances in understanding plant chromatid cohesion in the model plant Arabidopsis and crop plants and suggest how manipulation of crossover formation during meiosis, somatic DNA repair and chromosome folding may facilitate transmission of desirable alleles, tolerance to radiation and enhanced transcription of alleles that regulate sexual development. We hope that these findings highlight opportunities for crop breeding.